2행정 소형엔진의 대기오염물질 배출특성에 관한 연구 - 김필수(Pil-Su Kim); 최상진(Sang-Jin Choi); 박건진(Geon-Jin Park); 한용희(Yong-Hee Han); 김대곤(Dai-Gon Kim); 여소영(So-Young Yeo); 김정(Jeong Kim); 고지원(Ji-Won Goh); 장영기(Young-Kee Jang) (한국대기환경학회지, 2016)
In this study, pilot experiments were conducted by setting operation conditions to analyze characteristics of emission for air pollutant from small two-stroke engines. Emission factors of the measured concentration of pollutant were compared with EEA. Emission factor of CO analyzed by experiments - concentration, flow rate, fuel consumption, etc.- was estimated at 816,011 g-CO/ton-fuel in average. It was confirmed that more than 80% of the fuel consumption is discharged to the Carbon Monoxide, and that as the engine load becomes higher, emission factor of CO increases in the form of log function. The average emission factor of $NO_x$ and $PM_{10}$ was $3,801g-NO_x/ton-fuel$ and $3,730g-PM_{10}/ton-fue$l each. The deviation was not large by comparing the fuel-based emission factor of EEA and the result of this study. Since considerable pollutants are expected to be discharged from the small two-stroke engines, continuous research and support of the policy is required.